Cognitive instructional principles in elementary mathematics classrooms: a case of teaching inverse relations. Issue 8 (14th September 2021) - Ding, Meixia; Hassler, Ryan; Li, Xiaobao
ABSTRACT: Instructional principles gleaned from cognitive science play a critical role in improving classroom teaching. This study examines how three cognitive instructional principles including worked examples, representations, and deep questions are used in eight experienced elementary teachers' early algebra lessons in the U.S. Based on the analysis of 32 videotaped lessons of inverse relations, we found that most teachers spent sufficient class time on worked examples; however, some lessons included repetitive examples that also included irrelevant practice problems. Most teachers also situated new teaching in concrete contexts, which were faded into abstract representations. However, connections between concrete and abstract were not always made. The largest challenge was rooted in teachers' inability to ask deep questions that elicited students' deep explanations. Some teachers focused on key words and provided students with direct explanations. Implications are discussed.